Phosphoenolpyruvate Synthetase from the Hyperthermophilic Archaeon Pyrococcus furiosus - Hutchins, Andrea M. (American Society for Microbiology, 2001)
Phosphoenolpyruvate synthetase (PpsA) was purified from the hyperthermophilic archaeon Pyrococcus furiosus. This enzyme catalyzes the conversion of pyruvate and ATP to phosphoenolpyruvate (PEP), AMP, and phosphate and is thought to function in gluconeogenesis. PpsA has a subunit molecular mass of 92 kDa and contains one calcium and one phosphorus atom per subunit. The active form has a molecular mass of 690 ± 20 kDa and is assumed to be octomeric, while approximately 30% of the protein is purified as a large (∼1.6 MDa) complex that is not active. The apparent K(m) values and catalytic efficiencies for the substrates pyruvate and ATP (at 80°C, pH 8.4) were 0.11 mM and 1.43 × 10(4) mM(−1) · s(−1) and 0.39 mM and 3.40 × 10(3) mM(−1) · s(−1), respectively. Maximal activity was measured at pH 9.0 (at 80°C) and at 90°C (at pH 8.4). The enzyme also catalyzed the reverse reaction, but the catalytic efficiency with PEP was very low [k(cat)/K(m) = 32 (mM · s)(−1)]. In contrast to several other nucleotide-dependent enzymes from P. furiosus, PpsA has an absolute specificity for ATP as the phosphate-donating substrate. This is the first PpsA from a nonmethanogenic archaeon to be biochemically characterized. Its kinetic properties are consistent with a role in gluconeogenesis, although its relatively high cellular concentration (∼5% of the cytoplasmic protein) suggests an additional function possibly related to energy spilling. It is not known whether interconversion between the smaller, active and larger, inactive forms of the enzyme has any functional role.